Centre‐level variation in outcomes and treatment for otitis media with effusion and hearing loss and the association of hearing loss with developmental outcomes at ages 5 and 7 years in children with non‐syndromic unilateral cleft lip and palate: The Cleft Care UK study. Part 2. (June 2017) - Hall, A.; Wills, A. K.; Mahmoud, O.; Sell, D.; Waylen, A.; Grewal, S.; Sandy, J. R.; Ness, A. R.
Structured Abstract: Objectives: To explore centre‐level variation in otitis media with effusion (OME), hearing loss and treatments in children in Cleft Care UK (CCUK) and to examine the association between OME, hearing loss and developmental outcomes at 5 and 7 years. Setting and Sample Population: Two hundred and sixty‐eight 5‐year‐old British children with non‐syndromic unilateral cleft lip and palate (UCLP) recruited to CCUK. Materials and Methods: Children had air and bone conduction audiometry at age 5. Information on grommet and hearing aid treatment was obtained from parental questionnaire and medical notes. Hearing loss at age 5 was defined as >20 dB in the better ear and history of OME and hearing loss was determined from past treatment. Children with sensorineural hearing loss were excluded. Associations were examined with speech, behaviour and self‐confidence at age 5 and educational attainment at age 7. Centre variation was examined using hierarchical models and associations between hearing variables and developmental outcomes were examined using logistic regression. Results: There was centre‐level variation in early grommet placement (variance partition coefficient (VPC) 18%, P =.001) and fitting of hearing aids (VPC 8%, P =.03). A history of OME and hearing loss was associated with poor intelligibility of speech (adjusted odds ratio=2.87, 95% CI 1.42‐5.77) and aspects of educational attainment. Conclusions: Hearing loss is an important determinant of poor speech and treatment variation across centres suggest management of OME and hearing loss could be improved.